logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
Home  >>  CBSE XII  >>  Math  >>  Matrices
0 votes

Find $X$ and $Y$ if $(ii) \quad 2X + 3Y = \begin{bmatrix} 2 & 3 \\ 4 & 0 \end{bmatrix} \text{ and } 3X + 2Y = \begin{bmatrix} 2 & -2 \\ -1 & 5 \end{bmatrix} $

This question has 2 parts and each part has been answered separately here.
Can you answer this question?
 
 

1 Answer

0 votes
Toolbox:
  • The scalar multiplication $cA$ of a matrix $A$ and a number $c$ (also called a scalar in the parlance of abstract algebra) is given by multiplying every entry of $A$ by $c$.
  • The difference $A-B$ of two $m$-by-$n$ matrices $A$ and $B$ is calculated entrywise: $(A - B)_{i,j} = A_{i,j} - B_{i,j}$ where 1 ≤ i ≤ m and 1 ≤ j ≤ n.
Given $2X + 3Y = \begin{bmatrix} 2 & 3 \\ 4 & 0 \end{bmatrix} (i) $
Given $ 3X + 2Y = \begin{bmatrix} 2 & -2 \\ -1 & 5 \end{bmatrix} (ii)$
Multiplying (i) by 3 and (ii) by 2 and subtracting the two resulting equations:
$3(2X+3Y) - 2(3X+2Y) = 3 \begin{bmatrix} 2 & 3 \\ 4 & 0 \end{bmatrix} - 2 \begin{bmatrix} 2 & -2 \\ -1 & 5 \end{bmatrix} $
i.e., $6X+9Y-6X-4Y = \begin{bmatrix} 3\times2 & 3\times3 \\ 3\times4 & 0 \end{bmatrix} - \begin{bmatrix} 2\times2 & 2\times(-2) \\ 2\times(-1) & 2\times(5) \end{bmatrix} $
i.e., $5Y = \begin{bmatrix} 6 & 9 \\ 12 & 0 \end{bmatrix} - \begin{bmatrix} 4&-4 \\ -2& 10 \end{bmatrix} $
$5Y = \begin{bmatrix} 6-4 & 9-(-4) \\ 12-(-2) & 0-10 \end{bmatrix}$
$5Y = \begin{bmatrix} 2 & 13 \\ 14 & -10 \end{bmatrix}$
$Y = \frac{1}{5} \begin{bmatrix} 2 & 13 \\ 14 & -10 \end{bmatrix}$
$Y = \begin{bmatrix} \frac{2}{5} & \frac{13}{5} \\ \frac{14}{5} & -2 \end{bmatrix}$
Substituting $Y = \begin{bmatrix} \frac{2}{5} & \frac{13}{5} \\ \frac{14}{5} & -2 \end{bmatrix}$ in (i):
$2X + 3Y = 2X + 3 \begin{bmatrix} \frac{2}{5} & \frac{13}{5} \\ \frac{14}{5} & -2 \end{bmatrix} = 2X + \begin{bmatrix} 3\times\frac{2}{5} & 3\times\frac{13}{5} \\ 3\times\frac{14}{5} & 3\times(-2) \end{bmatrix}$$
$2X + 3Y = 2X + \begin{bmatrix} \frac{6}{5} & \frac{39}{5} \\ \frac{42}{5} & -6 \end{bmatrix} = \begin{bmatrix} 2 & 3 \\ 4 & 0 \end{bmatrix} $
Therefore, $2X = \begin{bmatrix} 2 & 3 \\ 4 & 0 \end{bmatrix} - \begin{bmatrix} \frac{6}{5} & \frac{39}{5} \\ \frac{42}{5} & -6 \end{bmatrix} $
i.e, $2X = \begin{bmatrix} 2- \frac{6}{5} &3 - \frac{39}{5} \\ 4-\frac{42}{5} &0-(-6) \end{bmatrix}$
i.e, $2X = \begin{bmatrix} \frac{4}{5} & -\frac{24}{5} \\ -\frac{22}{5} & 6 \end{bmatrix}$
$X = \frac{1}{2} \begin{bmatrix} \frac{4}{5} & -\frac{24}{5} \\ -\frac{22}{5} & 6 \end{bmatrix}$
$X = \begin{bmatrix} \frac{1}{2} \times \frac{4}{5} &\frac{1}{2} \times-\frac{24}{5} \\\frac{1}{2} \times -\frac{22}{5} & \frac{1}{2} \times6 \end{bmatrix}$
$X = \begin{bmatrix} \frac{2}{5} & \frac{-12}{5} \\ \frac{-11}{5} & 3 \end{bmatrix}$
answered Feb 27, 2013 by balaji.thirumalai
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...